Association of TDAP Vaccination With Acute Events and Adverse Birth Outcomes Among Pregnant Women With Prior Tetanus-Containing Immunizations. Issue 1 (January 2016) - Sukumaran, Lakshmi; McCarthy, Natalie L.; Kharbanda, Elyse O.; McNeil, Michael M.; Naleway, Allison L.; Klein, Nicola P.; Jackson, Michael L.; Hambidge, Simon J.; Lugg, Marlene M.; Li, Rongxia; Weintraub, Eric S.; Bednarczyk, Robert A.; et al.
Abstract : Obstet Gynecol Surv 2016;71(1):1–2 Neonates and infants are at increased risk of pertussis-related hospitalization and death. In 2012, the Centers for Disease Control and Prevention (CDC) Advisory Committee on Immunization Practices recommended tetanus, diphtheria, and acellular pertussis (TDAP) vaccination for all pregnant women during each pregnancy irrespective of prior immunization status.